Vegetation Dynamics and Sensitivity Responds to Climate Change in the Upstream of the Yellow River, China - XiangYu Lan; RuoWei Li; Xin Wang; TianCai Zhou; YunHui Li; JieJi Duo; Jian Sun (Ecosystem Health and Sustainability)
Although the upstream of the Yellow River (URYR) is an ecological security barrier to China, regional ecosystem functionings are pretty fragile and sensitive. Previous studies have provided much knowledge on linkages between vegetation dynamics and long-term climate change, but the vegetation sensitivity to short-term climate anomalies remains to be explored. Herein, we collected monthly normalized difference vegetation index (NDVI) and corresponding climate documents. We took advantage of the vegetation sensitivity index (VSI), trend analysis, and moving window to evaluate the spatiotemporal pattern of vegetation sensitivity in the URYR. Our results indicated that the higher and lower NDVI were observed in the western and eastern URYR, respectively, and that the NDVI in more than 89% area of the URYR experienced a positive change during the past 30 years. Furthermore, vegetation in the southwestern mountainous areas was more sensitive to climate variability, and the VSI was mainly dominated by temperature and surface solar radiation. Comparatively, the VSI in the northeast plain of URYR was low and governed by precipitation. Noticeably, significant increases (P < 0.05) in the interannual variability of VSI accounted for approximately 67% of regions. Generally, our findings highlight that more attention should be paid to the potential ecological risk areas (e.g., the southwestern URYR) with high temperature-sensitive vegetation (e.g., alpine meadow, alpine cushion vegetation, and alpine sparse vegetation). Our study is helpful to adaptive ecosystem management under ongoing climate change.